Development of macrolide resistance‐associated mutations after macrolide treatment in children infected withMycoplasma pneumoniae. Issue 11 (November 2017) - Suzuki, Yu; Shimotai, Yoshitaka; Itagaki, Tsutomu; Seto, Junji; Ikeda, Tatsuya; Yahagi, Kazue; Mizuta, Katsumi; Hongo, Seiji; Matsuzaki, Yoko
Abstract : Purpose. : To determine the timing of the emergence of macrolide‐resistant mutations after macrolide treatment in individuals with Mycoplasma pneumoniae infections. Methodology. : Between October 2011 and December 2013, serial pharyngeal swab specimens were collected before and after macrolide treatment from 21 otherwise healthy children infected with M. pneumoniae without macrolide‐resistant mutations. The copy numbers of a M. pneumoniae gene and the proportion of clones showing macrolide‐resistance mutations were determined for each specimen. Results. : After macrolide treatment (10‐15 mg kg −1 day −1 clarithromycin for 5‐10 days or 10 mg kg −1 day −1 azithromycin for 3 days), fever resolved in 19 (90%) of 21 children within 1 to 2 days, and the M. pneumoniae gene copy number decreased in all but one specimen in the second set of specimens relative to the number in the corresponding initial specimens. None of the second specimens, which were collected 2‐4 days after initiation of macrolide treatment, showed mutations in the 23S rRNA gene. However, the proportion of mutant clones with A2063G and A2064G mutations in the specimens collected 7‐24 days after initiation of treatment increased to 100%. We identified a family in which three members had M. pneumoniae infections. The analysis of transmission in this household indicated that the M. pneumoniae harbouring a macrolide‐resistant mutation that developed in the index patient after macrolide treatment was not transmitted to the family members. Conclusion. : A macrolide‐resistant population might develop in individual patients up to 24 days after initiation of macrolide treatment. However, the decrease in M. pneumoniae load after macrolide administration effectively reduces interpersonal transmission.